Biosurfactants of Lactic Acid Bacteria - Sharma, Deepansh; Saharan, Baljeet Singh; Kapil, Shailly; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides an introduction to biosurfactants produced by lactic acid bacteria, presenting a detailed compilation of their functional properties and structural composition. Microbial surfactants, extensively known as surface-active agents, have created a niche for themselves in the green-chemicals market, thanks to their distinct environment-friendly properties. The demand for biosurfactants in the cosmetics, food, pharmaceuticals, agricultural and environmental industries is steadily growing, and biosurfactants from lactic acid bacteria possess significant biological properties, making them potentially suitable for antimicrobial, anti-adhesive and various other industrially important applications. Exploring these aspects in depth, the book offers a valuable resource for both postgraduate students and researchers in the fields of food and industrial microbiology.
Introduction -- Biosurfactants of Probiotic Lactic Acid Bacteria -- Properties of Biosurfactants -- Structural Properties of Biosurfactants of Lab -- Substrates and Production of Biosurfactants -- Applications of Biosurfactants -- Future Prospect. .
Keywords: Life sciences; Biotechnology; Food -- Biotechnology; Microbiology; Life Sciences; Microbiology; Biotechnology; Food Science; Electronic books